Effect of Thickness and Dye on Optical and Photovoltaic Properties of Nanocrystalline TiO2 Thin Film for Dye Sensitized Solar Cell Application - Sarode1, M.T.; Khollam3, Y.B.; Jadkar2, S.R.; Kale4, B.B.; Mohite2, K.C. (Asian Journal of Chemistry, 2013)
Different thickness of dye sensitized solar cells of TiO2 thin films prepared by modified sol-gel method with Eosin-Y and Rose Bengal dyes are investigated in present communication. As deposited films 1, 3 and 5 layer coating were annealed 400 ºC/2 h. The resultant films were characterized by using XRD, Raman spectroscopy, SEM, TEM and UV-visible spectroscopy. The structural studies revealed the evolution of pure anatase TiO2 phase in resultant films. The morphological studies with SEM indicated nearly uniform size distribution of spherical agglomerates in resultant films. The TEM studies indicated nanocrystalline state of films (average particle size ~ 25 nm) consistent with XRD results of crystallite size = 20-30 nm. The better optical properties: indirect band gap energy, absorbance coefficient, transmittance, refractive index and porosity ratio are 3.22 eV, 2.8 × 104 cm-1, 86 %, 2.02 and 43.50 % respectively of the 5 layer coating film annealed at 400 ºC/2 h. The better photovoltaic performance: VOC = 0.70 V, JSC = 1.82 mA/cm2, FF = 68.3 % and h = 0.87 % using Eosin-Y dye with polyiodide electrolyte are obtained for the dye sensitized solar cells of TiO2 films generated from 5 layer coated film annealed at 400 ºC/2 h. The conversion efficiency increases with increasing thickness of film and it is greater for Eosin-Y than Rose Bengal dye.